A Study on the Challenges and Opportunities in the Way of Aatamnirbhar Bharat: Enhancing Economic Development in Indian Agriculture (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The efficient state of various provincial ranchers is getting lower and henceforth, various methodologies should be made with the goal that the status of the country ranchers of India can be improved. In India, a large portion of the country ranchers are intensely depended on the rural exercises.In the event that in their regions, insufficient water is encouraged or downpour level lessening then these ranchers need to confront a ton of challenges while the creation of the harvests as in a large portion of the occasions, on diminishing the degree of water and stormy season, the general yield creation of the ranchers will in general decline. Thus, Indian government is likewise looking to give different chances to the ranchers with the goal that their efficient advancement should be possible no problem at all.